Cover Feature: Porous Carbon Networks Decorated with Cobalt on CoFe2O4 as an Air‐Breathing Electrode for High‐Capacity Rechargeable Lithium‐Air Batteries: Role of Metallic Cobalt Nanoparticles (ChemElectroChem 20/2020). Issue 20 (23rd September 2020) - Athika, Mattath; Elumalai, Perumal
Abstract : The Cover Feature illustrates use of a Co/CoFe2 O4 ‐decorated porous carbon network as an air‐breathing electrode for high‐capacity rechargeable lithium–air batteries. More information can be found in the Article by M. Athika and P. Elumalai .